(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article analyzes the features of parliamentary elections in Kyrgyzstan during the period of 1995–2000 and their impact on the development of the political system. The study examines the formation of political parties at that time, their role in the electoral process, and their place in the democratic development of the country. Particular attention is given to the use of the majoritarian electoral system and its influence on political competition. The role of administrative resources in the organization of elections and the participation of international organizations as observers are also explored. In conclusion, the article identifies the characteristics of political culture shaped through electoral processes and the trends in the development of the party system. The study covers the organizational specifics of the electoral process, the development of the legal framework, and the dynamics of political actors. Moreover, the work provides important theoretical and practical insights for understanding Kyrgyzstan’s political transformation during the transitional period.